Obtenção de filmes fotocatalisadores por oxidação eletrolítica assistida por plasma (PEO) sobre titânio metálico - Corrêa, Mateus Tofoli (2021)
The literature demonstrates the use of irradiated semiconductors in the treatment of effluents in a process called heterogeneous photocatalysis, a variant of advanced oxidative processes. The applicability of semiconductors is due to their electronic structure, characterized by bands that, when excited, present charges with redox potential capable of promoting various chemical reactions. TiO2 is the most studied semiconductor oxide for this purpose, however, it is limited by the high rate of recombination of photogenerated charges, which reduces its potential. Another limiting factor is the recovery of the catalyst when it is formed by small particles on the nanometer scale. One way to facilitate the recovery and reuse of the material is by applying them in the form of a film. In this context, using a metallic titanium (Ti) plate in a plasma-assisted electrolytic oxidation (PEO) process allows the formation of a thin layer of its oxide, the semiconductor titanium dioxide (TiO2) on the metal. Also, recent research demonstrates the incorporation of other materials, such as tin dioxide (SnO2), to assist TiO2 during photocatalysis, by forming heterostructures, which act to reduce the rate of recombination of photogenerated charges. Thus, this work aimed to study the applicability of the PEO process in obtaining TiO2 photocatalyst films and the incorporation of SnO2 in the structure by adding it in the form of particulate material to the electrolyte during the PEO process. The application of sulfuric and phosphoric acid in the electrolyte, as well as different concentrations of SnO2 in it, were studied. The characterization of the films was performed using the techniques of atomic force microscopy (AFM), scanning electron microscopy coupled with energy dispersive spectroscopy (SEM/EDS) and X-ray diffractometry. The characterization tests showed the influence of the electrolyte on the crystalline phase obtained, as well as on the surface morphology of the film. The incorporation of SnO2 in the final structure could not be verified, indicating that the concentration used was not sufficient for this purpose. Heterogeneous photocatalysis tests on the degradation of rhodamine B and methylene blue dyes under UV radiation showed the applicability of PEO in obtaining photocatalyst films. The films obtained via PEO showed activity after 4 cycles, indicating the applicability of the process to obtain photocatalyst films with the possibility of recovery and reuse.